1993
DOI: 10.1111/j.1532-849x.1993.tb00399.x
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Bonding Titanium Restorations

Abstract: It was concluded that titanium bonded restorations with certain adhesive cements were a definite possibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Ti alloy provide a more stable oxidation layer (Craig & Powers 2004). The tensile bond strength of cements was similar in all alloys tested, a result similar to a study by but unlike the studies of Lorey et al (1993) and that with a different methodology found a shear strength of Panavia F cement higher when used with C.P. Ti alloy.…”
Section: Resultssupporting
confidence: 85%
“…Ti alloy provide a more stable oxidation layer (Craig & Powers 2004). The tensile bond strength of cements was similar in all alloys tested, a result similar to a study by but unlike the studies of Lorey et al (1993) and that with a different methodology found a shear strength of Panavia F cement higher when used with C.P. Ti alloy.…”
Section: Resultssupporting
confidence: 85%
“…Titanium is attractively characterized by its high corrosion resistance and less allergic reaction when compared to other base metal alloys. Although the development of casting technology has made it possible to fabricate prostheses with titanium, it still remains a problem to achieve a durable bond between titanium and luting materials (1). When a conservative abutment design is adopted for resin-bonded ®xed partial denture, eective adhesive bonding is needed to ensure an adequate time of prosthodontic service.…”
mentioning
confidence: 99%
“…Titanium is a useful option for fabricating cast restorations1–3 and denture bases4–6 when a patient is allergic to other metal elements 7. Strong and durable bonding between the metal framework and the luting material is essential for applying titanium to a resin‐bonded‐fixed partial denture 8…”
Section: Introductionmentioning
confidence: 99%